Perancangan Desain UI/UX Aplikasi Findchise Menggunakan Metode User Centered Design (UCD) - Fitri, Maulidya Firdausy Al; Afandi, Mohamad Irwan; Fitri, Anindo Saka (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Franchise is a partnership model that is growing rapidly in Indonesia, offering business opportunities for small and medium entrepreneurs. However, there is currently no mobile application available that provides a platform to connect franchisees and franchisors. This study aims to develop a mobile application, Findchise, with a focus on user needs through the User Centered Design (UCD) method. The evaluation results of the System Usability Scale (SUS) after improvements showed an increase in the average SUS score to 93.5 for franchisees and 89.5 for franchisors. Both scores fall into the “Excellent” category with a grade of A and an acceptability level of acceptable. These findings indicate that the UI/UX design of Findchise successfully meets user needs and provides a user-friendly experience